LINK TO COMPLEX SUBJECT POLYPREDICATIVE UNITS - D. R. Teshaboyev (Modern American Journals, 2025)
This article analyzes complex subordinate clause polypredicative units, their emergence with various grammatical means, semantic and structural features of compound sentences that perform different syntactic functions in relation to the first part, and at the same time, scientific views and conclusions are given on the discovery of new aspects of complex subordinate clause polypredicative units.
Keywords: Compound sentence, complex subordinate clause, subordinate clause without a conjunction, subordinate clause, main predicative clause, subordinate predicative clause, syntactic relation, tone.